Blinde Flecken der Entwicklungszusammenarbeit : Zur Kooperationspraxis lokaler Non-Profit-Organisationen in Bolivien. - Beckmann, Gabriele (Global Studies., 2016)
Why does organisational support in the area of developmental co-operation often fail? A multi-dimensional analysis of concrete case studies.